Ligands of the peroxisome proliferator-activated receptors (PPAR-gamma and PPAR-alpha) reduce myocardial infarct size - Wayman, NS (2015)
This study was designed to investigate the effects of various chemically distinct activators of PPAR-gamma and PPAR-alpha in a rat model of acute myocardial infarction. Using Northern blot analysis and RT-PCR in samples of rat heart, we document the expression of the mRNA for PPAR-gamma (isoform 1 but not isoform 2) as well as PPAR-beta and PPAR-alpha in freshly isolated cardiac myocytes and cardiac fibroblasts and in the left and right ventricles of the heart. Using a rat model of regional myocardial ischemia and reperfusion (in vivo), we have discovered that various chemically distinct ligands of PPAR-gamma (including the TZDs rosiglitazone, ciglitazone, and pioglitazone, as well as the cyclopentanone prostaglandins 15D-PGJ(2) and PGA(1)) cause a substantial reduction of myocardial infarct size in the rat. We demonstrate that two distinct ligands of PPAR-gamma (including clofibrate and WY 14643) also cause a substantial reduction of myocardial infarct size in the rat. The most pronounced reduction in infarct size was observed with the endogenous PPAR-gamma ligand, 15-deoxyDelta(12,14)-prostagalndin J(2) (15D- PGJ(2)). The mechanisms of the cardioprotective effects of 15D- PGJ(2) may include 1) activation of PPAR-alpha, 2) activation of PPAR-gamma, 3) expression of HO-1, and 4) inhibition of the activation of NF-kappaB in the ischemic-reperfused heart. Inhibition by 15D- PGJ2 of the activation of NF-kappaB in turn results in a reduction of the 1) expression of inducible nitric oxide synthase and the nitration of proteins by peroxynitrite, 2) formation of the chemokine MCP-1, and 3) expression of the adhesion molecule ICAM-1. We speculate that ligands of PPAR-gamma and PPAR-alpha may be useful in the therapy of conditions associated with ischemia-reperfusion of the heart and other organs. Our findings also imply that TZDs and fibrates may help protect the heart against ischemia-reperfusion injury. This beneficial effect of 15D- PGJ(2) was associated with a reduction in the expression of the 1) adhesion molecules ICAM-1 and P-selectin, 2) chemokine macrophage chemotactic protein 1, and 3) inducible isoform of nitric oxide synthase. 15D- PGJ(2) reduced the nitration of proteins (immunohistological analysis of nitrotyrosine formation) caused by ischemia-reperfusion, likely due to the generation of peroxynitrite. Not all of the effects of 15D-PGJ(2), however, are due to the activation of PPAR-gamma. For instance, exposure of rat cardiac myocytes to 15D-PGJ(2), but not to rosiglitazone, results in an up-regulation of the expression of the mRNA for heme-oxygenase-1 (HO-1). Taken together, these results provide convincing evidence that several, chemically distinct ligands of PPAR-gamma reduce the tissue necrosis associated with acute myocardial infarction.